Locust and Grasshopper Management - Zhang, Long; Lecoq, Michel; Latchininsky, Alexandre; Hunter, David (Annual review of entomology, 2019)
Locusts and grasshoppers (Orthoptera: Acridoidea) are among the most dangerous agricultural pests. Their control is critical to food security worldwide and often requires governmental or international involvement. Although locust and grasshopper outbreaks are now better controlled and often shorter in duration and reduced in extent, large outbreaks, often promoted by climate change, continue to occur in many parts of the world. While some locust and grasshopper control systems are still curative, the recognition of the damage these pests can cause and the socioeconomic consequences of locust and grasshopper outbreaks have led to an increasing paradigm shift from crop protection to preventive management. Effective preventive management strategy relies on an improved knowledge of the pest biology and ecology and more efficient monitoring and control techniques.